2003
DOI: 10.1103/physrevlett.90.086101
|View full text |Cite
|
Sign up to set email alerts
|

Water in Contact with Extended Hydrophobic Surfaces: Direct Evidence of Weak Dewetting

Abstract: X-ray reflectivity measurements reveal a significant dewetting of a large hydrophobic paraffin surface floating on water. The dewetting phenomenon extends less than 15 A into the bulk water phase and results in an integrated density deficit of about one water molecule per 25-30 A(2) of water in contact with the paraffin surface. The results are supported by molecular dynamics simulations and related to the hydrophobic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
231
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(262 citation statements)
references
References 30 publications
29
231
2
Order By: Relevance
“…Neutron [547] and X-ray [548] reflectivity experiments confirmed the observed reduced density of water at the interface, while experiments with an ellipsometer excluded nanobubbles on silanated silica [549]. There is now strong evidence, that bridging bubbles contribute to the long-range hydrophobic attraction in many experiments [495] but the whole hypothesis and the effect of nanobubbles are still being debated [550].…”
Section: Hydrophobic Attractionmentioning
confidence: 58%
“…Neutron [547] and X-ray [548] reflectivity experiments confirmed the observed reduced density of water at the interface, while experiments with an ellipsometer excluded nanobubbles on silanated silica [549]. There is now strong evidence, that bridging bubbles contribute to the long-range hydrophobic attraction in many experiments [495] but the whole hypothesis and the effect of nanobubbles are still being debated [550].…”
Section: Hydrophobic Attractionmentioning
confidence: 58%
“…For example, neutron reflectivity measurements of Steitz et al (2003) investigated the contact between water and polystyrene and concluded that there is a surface layer 2-5 nm thick with a density 6-12% lower than that of the bulk. Other workers ( Jensen et al 2003) using X-ray reflectivity also found a depletion layer next to an alkane monolayer, with a similar density deficit of ca. 10%; the layer thickness is, however, less than 1.5 nm.…”
Section: Water In Different Environmentsmentioning
confidence: 92%
“…All this is consistent with a nonpolar layer of hydrophobic material atop the water surface. Hydrophobicity induced drying [Jensen et al, 2003;Ma et al, 2007] may serve as an explanation for the presence of dangling OH bonds at such interfaces. According to this, in order to keep the hydrophobic surface dewetted, water is not able to maintain its four coordination hydrogen-bonding configuration and forms a dangling OH bond pointing toward the hydrophobic surface.…”
Section: Polluted Harbor and Diesel Fuel Samplesmentioning
confidence: 99%
“…Even for a fully covered surface, the red-shifted dangling bond continued to persist and was interpreted to belong to water that is in contact with an extended hydrophobic surface. According to an effect called hydrophobicity induced drying [Jensen et al, 2003;Ma et al, 2007], water exhibits a structure with hydrogen bonds still pointing toward the hydrophobic surface.…”
Section: Role Of Confined Watermentioning
confidence: 99%